The review of Variables Related to Problem Solving Skills in PISA 2003-2012 of Turkey - Duygu İleritürk; Remzi Yavaş Kıncal (Sakarya University, 2016)
This study is aimed to review the results of problem solving skills test in PISA of Turkey in terms of gender, curriculum and types of school. The data was analyzed by the means of document analysis method in this study which has a qualitative descriptive research design. The reports published by OECD and MEB were used as data collection instruments, and also articles, master thesis and dissertations and reports, which have open access and are published in national and foreign literature in 2004-2014, were used to interpret in these data in the study. According to findings, Turkey has been located at the proficiency level 2 in both PISA 2003 and 2012 in terms of mathematical literacy, and moreover there is a difference between the score point and ranking of success but any development has been not seen on proficiency level. The findings in the study are evaluated according to gender, types of school and curriculum published in 1995 and 2004. According to the results of the study, both PISA 2003 and 2012 is seen to have difference in score and ranking, there is no difference at the proficiency levels. When the results is analyzed in terms of variables of the study, the most successful school type in PISA 2003 is science high school while the students from vocational high school are more successful in problem solving than the other field in PISA 2012. Male students have been more successful than female students in both PISA 2003 and 2012, but it has been showed that there is no a significant difference statistically between them.